Synergistic effect of dielectric resonance and plasma oscillation on negative permittivity behavior in La1-xSrxMnO3 single-phase ceramic. Issue 6 (15th March 2022) - Sun, Kai; Yang, Pengtao; He, Qifa; Fan, Runhua; Wang, Zongxiang; Tian, Jiahong; Yang, Xuechun; Duan, Wenxin; Wu, Xinfeng; Wang, Zhongyang
Abstract: Ceramic-based composites with negative permittivity property can be realized by dielectric resonance or plasma oscillation, but it is still a challenge to integrate two kinds of negative permittivity into a single-phase material. In this study, the La1- x Sr x MnO3 (LSMO) single-phase ceramic ( x  = 0.3, 0.4, 0.5, 0.6 and 0.7) was successfully fabricated by a sol-gel auto-combustion and pressureless sintering method. Just by adjusting the content of Sr 2+, the Lorentz-like and Drude-like negative permittivity were simultaneously observed in LSMO ceramic under the synergistic effect of dielectric resonance and plasma oscillation. The amplitude of dielectric resonance was lessened because of the increase of damping factor, and the resonance frequency gradually moved to a lower frequency region with the increase of Sr 2+ . When the content of Sr 2+ reached 0.7, the Drude-like negative permittivity played an overwhelming role due to an enhanced double-exchange effect in La1- x Sr x MnO3 . Meanwhile, the tan δ of LSMO was as low as 0.085, which was scarcely observed in previous investigations. The generation and regulation mechanism of negative permittivity was further clarified. This work opened up a way to adjust negative permittivity behavior in single-phase ceramic material which has great value in high-power microwave filters and wireless ring resonators.